Mapping Intermediality in Performance - Nelson, Robin; Lavender, Andy; Bay-Cheng, Sarah; Kattenbelt, Chiel (MediaMatters, 2010)
This volume examines afresh the impact upon acting and performance of digital technologies. It is concerned with how digital culture combines the traditional 'liveness' of theatre with media interfaces and internet protocols. The time and space of the 'here and now' are both challenged and adapted, just as barriers between theatre-makers and the 'experiencers' of events are broken down. Today many of us are everyday players performing the interconnectedness of digital culture and a key aim of the book is to unpack the multiple interrelations within the landscape of contemporary performance. Access to a range of 'instances' (The Builders Association, Castellucci, Castorf, Gob Squad, Lepage, Second Life and VJing) is through 'portals' which afford perspectives on the main characteristics of theatre and performance in the digital age.